Uttarakhand Third Five-Year Plan Brief Progress Report 1964-65 (Third Quarter October—December) - Planning Commission (Planning Commission, 1964)
Expansion of Multi-purpose Horticulture Farms—All the 11 existing Horticulture Farms and the newly established nine Model Orchards (8 in Pithoragarh and one in Uttarkashi district) of about five acres each established at the Block Headquarters continued to function. During the quarter under report preliminary work for setting up the nine model orchards (8 in Chamoli and one in Uttarkashi district) sanctioned during the preceding quarter was started.